2004
DOI: 10.1021/ie0497644
|View full text |Cite
|
Sign up to set email alerts
|

Copper Nanoparticle Synthesis in Compressed Liquid and Supercritical Fluid Reverse Micelle Systems

Abstract: Synthesis of copper nanoparticles within sodium bis(2-ethylhexyl)sulfosuccinate (AOT) reverse micelles was performed by implementing compressed liquid and supercritical fluid (SCF) alkanes as the bulk solvent of the microemulsion system. In this reverse micelle reaction media, the role of the anionic surfactant AOT is twofold. Initially, the AOT creates a thermodynamically stable microemulsion system consisting of water and metal ions encased within an AOT surfactant reverse micelle and dispersed within a bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 37 publications
2
38
0
2
Order By: Relevance
“…In w/o microemulsions, the most popular choice of surfactant is AOT and for most liquid/supercritical alkanes, AOT can still be applied. 62,138,144 However, when using liquid or supercritical CO 2 , AOT will not form stable microemulsions alone, being of low compatibility with the continuous CO 2 phase (discussed in chapters 3 and 7). Fluorinated co-surfactants, such as PFPE-PO 4 (perfluoropolyether-phosphate) [141][142][143]147 or F-pentanol 139,148 must be employed to stabilize the dispersions.…”
Section: Methodsmentioning
confidence: 99%
“…In w/o microemulsions, the most popular choice of surfactant is AOT and for most liquid/supercritical alkanes, AOT can still be applied. 62,138,144 However, when using liquid or supercritical CO 2 , AOT will not form stable microemulsions alone, being of low compatibility with the continuous CO 2 phase (discussed in chapters 3 and 7). Fluorinated co-surfactants, such as PFPE-PO 4 (perfluoropolyether-phosphate) [141][142][143]147 or F-pentanol 139,148 must be employed to stabilize the dispersions.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, studies have been done to predict the particle size that can be stabilized at given conditions in conventional liquid solvents 23 , supercritical ethane 24 , compressed propane 25 and supercritical CO 2 26 . Shah et al 24 initiated this soft sphere modeling approach, where stabilization of nanoparticles in a given solvent depends on the balance between the van der Waals attractive forces with steric repulsive forces.…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…There is experimental evidence that thiol tails on a metal surface are in the extended mode. For example, using IR spectroscopic and ellipsometric data, Porter et al 39 have shown that thiol tails with hydrocarbon group (-CH 2 ) greater than 9 assemble on gold surfaces in a densely packed manner with fully extended alkyl chains tilted from the surface normal by [20][21][22][23][24][25][26][27][28][29][30] o . This suggests that the Condensed Phase Model may not be the correct phenomenological model for our experimental system.…”
Section: Condensed/collapsed Phase Model (Cpm)mentioning
confidence: 99%
“…Above that pressure, the average size of the silver nanoparticles remained virtually constant with smaller standard deviations. Synthesis of copper nanoparticles in reverse micelles was performed by Kitchens and Roberts [18] using compressed liquid and supercritical fluid alkanes as the bulk solvent. The size of the nanocrystals was found to increase with pressure.…”
mentioning
confidence: 99%
“…Tuning of CdS nanoparticles by density variation appears to work well at short reaction times where the exchange-channel mechanism and the micellar-templating effect dominate. For very long reaction times, as the nanoparticles grow larger, the surfactant might act as a dispersant ligand [18] and www.chemeurj.org sterically stabilizes the nanoparticles without involving the microemulsion. Conversely, in the case of ZnS nanoparticles, the reaction time seems not to affect the final particle size.…”
mentioning
confidence: 99%